The Use of Google Classroom in Physics Course: Students' Perception - Furqon, Muhammad; Sinaga, Parlindungan; ., Liliasari; Septem Riza, Lala (KnE Social Sciences, 2024)
The use of the learning management system (LMS) in online learning has impacted the development of science and technology in the field of education. One of the major LMS that is frequently used today is Google Classroom. This study intends to evaluate student impressions of utilizing Google Classroom as an LMS in online physics learning. The method utilized by the researcher is the qualitative method. A total of 12 physics education students from one of the universities in Indonesia were involved as respondents in the interviews performed. The interview data were evaluated through the stages of organization, transcription, exploration, coding, theme formulation, and description based on the theme. The conclusions in this study consist of advantages, disadvantages, challenges, and suggestions for Google Classroom as an LMS relating to accessibility, connectivity, features, navigation, notifications, data plans, bandwidth, device memory, and display. A further study employing more respondents or from a teachers’ or lecturers’ perspective can be undertaken to provide a more comprehensive understanding of student perceptions of using Google Classroom as an LMS. Keywords: google classroom, physics course, students’ perception